FAKTOR-FAKTOR YANG MEMPENGARUHI TINGKAT SUKU BUNGA DEPOSITO BERJANGKA PADA BANK UMUM DI INDONESIA (Studi Empiris Pada Bank Umum yang Go Public di BEI Tahun 2011-2015) - Resty Septiana; Abd. Kodir Djaelani; M. Khoirul ABS (UNIVERSITAS ISLAM MALANG, 2017)
This research has a purpose to determine the effect of inflation, Capital Adequacy Ratio, Return on Assets, and Loan to Deposit Ratio on interest rates of time deposit in commercial banks in Indonesia in 2011-2015. The sample selection using purposive sampling method. The data used in this research was obtained from the financial statements Publication 2011-2015. The results showed that (1) Inflation, Capital Adequacy Ratio, Return on Assets and Loan to Deposit Ratio affect the interest rates on time deposits. (2) Partially showed that inflation variable positive influence and significance of the level of interest rates on time deposits, CAR variabel positive effect and significance of the level of interest rates on time deposits, ROA and LDR variabel negative and not significant to the deposit interest rate futures.